Assessing the impact of fiscal policy on investment and economic growth: Evidence from a Panel of Six Arab Economies, 1970–2023 - ALI, Walid; ABIDA, Zouhair (International journal of economic perspectives, 2025)
In this article, we investigate the influence of corporate profit imposition on economic growth based on an endogenous growth model. The preferred economic tool is the panel smooth transition model (PSTR), which is based on the composition of the fiscal structure. The study covers the period from 1970 to 2023 and focuses on six (6) Arab countries in the West African Economic. The findings show that the imposition of corporate profits has a beneficial effect on the economy when the rate of delayed imposition for a given period is increased. In this case, fiscal policy is effective. However, when the level of corporate profit taxation exceeds the critical threshold, the influence of taxation policy on growth becomes negative. To that end, we propose a tax system that is less distorting, disproportional, targeted, and democratic.